ПРОБЛЕМА ЯЗЫКА И РЕАЛЬНОСТИ В ЛИНГВИСТИЧЕСКИХ И ФИЛОСОФСКИХ ИССЛЕДОВАНИЯХ (Filološke pripombe, 2019)
The problem «language and reality» should be revolved by the new side, namely: whether to be capable human language by a reliable support on ways of ascension from individual to general, from the infinite world of concrete things to knowledge of the world as whole: to be not a barrier, but instrument of knowledge of infinity, its primary factor. In essence, the scientists should theoretically prove that language in practice, actually already makes, as it is a condition of existence of all sciences, in particular – philosophical discussions about infinity of the world – it is necessary to show, that before theoretical discussions about infinity, language already deduces the man to infinity by the it’s forms.